Działalność biblioteki dla osób niewidomych i słabowidzących w Zurychu = The activities of the library for the blind and visually impairedin Zurich - Kuczyńska-Kwapisz, Jadwiga (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
In June of this year (2016), I had the opportunity to visit and find out about the performance and activities of the Swiss Library for the Blind and Visually Impairedin Zurich (Schweizerische Bibliothek für Blinde und Sehbehinderte [SBS]). The library was founded in 1903 as a non-profit organization. It provides all sorts ofliterature for the blind, visually impaired and reading disabled. They lend out books and notes written in Braille, as well as large-print books, e-books, audio books,journals published in Braille, and recorded ones. There are also various kinds of game with Braille description or features ? both educational and entertaining ones. This is an uncommon practice; indeed, I have not met with this type of activityin other libraries designed for blind people. The activities there are not limited tolending, but also include production. They themselves create audiobooks and other materials for listening, or for printed magazines, as well as various types of text. They also issue music tracks transcribed into Braille musical notation, books with various sizes of large print, e-books, films with special descriptions (in coopera-tion with film studios and television stations), educational aids, and scientific andspecialist literature (primarily as e-texts). They realize a variety of different orders. For example, in Switzerland it is more common, compared to other countries, to hold referendums at a national level as well as in the cantons. It is important that people with sight-related disabilities then participate on an equal basis. The Swiss Library for the Blind and Visually Impaired in Zurich (Schweizerische Bibliothekfür Blinde und Sehbehinderte [SBS]) prepares the relevant documents. Another important activity is the presentation of special cases and problems pertaining to the blind for the broader Swiss society. To fulfill this aim, the library organizes an open day and issues special materials every year.
Keywords: biblioteka w Zurychu; niewidomi i słabowidzący w bibliotece; osoby niesłyszące; produkcja materiałów bibliotecznych; świadomość społeczna; library in Zurich; blind and partially sighted people in the library; deaf people; production of library materials; social awareness